Strengthening the strategic capacity of public universities: The role of internal governance models. (October 2019) - Frølich, Nicoline; Christensen, Tom; Stensaker, Bjørn
Governments in Europe have emphasized the development of more autonomous public universities over the last couple of decades. Often, the aim of these reform policies has been to stimulate to a more competitive and agile higher education sector, where increased formal autonomy is perceived as a key condition to strengthen the strategic capacity of universities. These reforms have resulted in considerable shifts in the internal governance models of some universities, while others have kept their traditional governance models. In this article, instrumental and cultural perspectives derived from organizational theory are used as lenses to compare how universities with different internal governance models organize and structure their strategic development processes. Our findings suggest that internal governance models have little impact on the design and organization of strategic processes. In conclusion, it is argued that changes in internal governance arrangements alone are not enough to drive transformation in higher education institutions, and the issue of formal institutional autonomy is intimately linked to how various policy instruments at the system level are designed and coordinated.